Community-based Adaptation : Lessons from a Grant Competition - Heltberg, Rasmus; Gitay, Habiba; Prabhu, Radhika G. (Taylor and Francis, 2013)
What do local communities perceive as the key problems and challenges for adaptation to climate change? Lessons are identified from a major global grant competition, the Development Marketplace, focused on adaptation to climate change. Proposals developed by non-governmental actors at the local level were informed by deep concerns that on-going climate change and its impacts undermine development and exacerbate poverty, migration and food insecurity. Drought and floods were the most commonly identified climate risks. Adaptation proposals simultaneously addressed local poverty and climate change challenges, and offered a wide range of approaches to render local development more resilient to current climate variability. The findings have important implications for the design of support to community-based adaptation, which should exploit its strong local grounding and synergies with development; help connect local initiatives to higher levels; and use complementary approaches to address policy issues.